2021
DOI: 10.46309/biodicon.2021.927104
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Nitrogen Doses on Yield and Yield Components of Basil (Ocimum basilicum L.) Plant

Abstract: In this study, it is aimed to determine the effect on yield and yield components of basil (Ocimum basilicum L.) of different nitrogen doses (0, 3, 6, 9, 12 and 15 kg da -1 ). The study was carried out in a randomized complete block design with three replications under Eskişehir ecological conditions in 2019-2020. The plant height, fresh herb yield, fresh and dry leaf yields, essential oil content and essential oil yield of Ocimum basilicum L. were investigated in the study and the effect of different nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This result was expected because the plant received additional nutrients for growth from the used fertiliser. Many authors (Katar et al, 2022;Sazhina et al, 2020) have found a similar influence of fertilisers on the development of buckwheat. However, some authors also found that fertilisation can reduce yield.…”
Section: Resultsmentioning
confidence: 73%
“…This result was expected because the plant received additional nutrients for growth from the used fertiliser. Many authors (Katar et al, 2022;Sazhina et al, 2020) have found a similar influence of fertilisers on the development of buckwheat. However, some authors also found that fertilisation can reduce yield.…”
Section: Resultsmentioning
confidence: 73%
“…Through manipulation of cultural practices, such as weed and disease control, early sowing, fertilization and seed treatments, it is possible to increase yields of the crops. It has been reported that earlier sowing (Yau, 2007;Keles and Ozturk, 2012;Hatipoglu et al, 2012) and application of different fertilizers (Tuncturk and Yildirim, 2004;Katar et al, 2012;Ekin, 2020) increased seed and oil yield in safflower. Different seed treatments including inoculation with plant growth promoting bacteria, have also been used to increase germination, seedling establishment, and crop productivity and quality under normal or stress conditions in many different crop species including safflower (Naseri and Mirzaei, 2010;Nosheen et al, 2016;Nosheen et al, 2018a;Khademian et al, 2019;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 96%